Reforma procesal civil en el Perú: Hacia un proceso efectivo de restitución de bienes inmuebles por vencimiento de plazo del contrato de arrendamiento y por falta de pago de la renta - Martel Chang, Rolando A. (2025)
The author presents the proposal from the Working Group tasked with revising the Civil Procedure Code, focusing on improving the effectiveness of proceedings for the repossession of real estate properties due to expired leases or non-payment of rent. The proposal is based on the incorporation of the summary proceeding and the expedited proceeding, each with its own set of general and special rules.